Regionalwährungen in Deutschland: Lokale Konkurrenz für den Euro? - Gerhard Rösl (Deutsche Bundesbank, 2006)
In a surprisingly growing number of regions in Germany private "regional currencies" are issued as a cash substitute for the euro. Currently, these regional currencies are conceived almost exclusively as Schwundgeld (depreciative currency), which loses value on a predetermined timescale. This loss of value is intended to encourage the money owners to spend their money quickly in order to boost local demand. The paper shows that the issuance of unofficial parallel currencies is not a fundamentally new phenomenon neither in Germany nor in other European countries. The theoretical assumptions of the Schwundgeld concept (Silvio Gesell (1862 – 1930)) are highly flawed and suboptimal from a welfare-theoretical perspective. However, the current economic welfare losses resulting from the issuance of Schwundgeld are negligibly small.
Keywords: E50; E42; E41; E40; 330; Regionalwährungen; Regionalgeld; Parallelgeld; Gesell; Währungssubstitution; Schwundgeld; Freigeld; currency substitution; private money; Währungswettbewerb; Freiwirtschaft; Wohlfahrtseffekt; Schätzung; Deutschland